Implementasi Metode Ummi dan Implikasinya Terhadap Kualitas Hafalan Al-Qur’an Siswa MADIN Muhammadiyah Bae Kudus - Lukman Hakim; Zahrotul Inayah; Muhammad Lutfi Al Fatih; Moh Sholihudin (TAUJIH: Jurnal Pendidikan Islam, 2025)
This research is motivated by the existence of the Tahfidz Al Qur’an education program at Madrasah Diniyah Bae Kudus, which uses ummi method and has so far been considered successful in producing graduate or fairly good quality. This study aims to examine the implementation of the Tahfidz Program using the Ummi method at Madrasah Diniyah Bae, to observe the supporting and inhibiting factors in the Tahfidz learning procces at the institution, and to identify the implications of using the ummi method on the quality of sudents’ Qur’an memorization. This research uses a qualitative methode with a field study approach. Data were collectted through interviews, observations, and documentation. Data analysis was carried out using data reduction, data presentation and conclusion. This researchbroadly reveals facts the activities in the Ummi method includes the opening, apperception, concept introduction, concept understanding, skills/practice, evaluation, and closing. The implementation of learning using the Ummi method, there are several supporting and inhibiting factors. The inhibiting factors include students often lacking concentration or feeling sleepy during the learning process. Additionally, there are challenges in the muraja’ah process at each student’s home, which is difficult to monitor or supervise. On the other hand, one of the supporting factors in the learning process using the ummi method is the use of media as alearning aid. Based on observations and analysis of student’s learning achievement data, it can be concluded that the Ummi methode has a positive impact in helping improve the quality of students’ Qur’an memorization.